Experimental studies of dieless forming - Hrairi, Meftah; Nawi, Saiful Mazwan (IIUM Press, 2011)
Manufacturing new products brings new challenges to the product introduction and commissioning process. In traditional sheet metal forming, the tooling costs are a drawback especially for bespoke and small batch manufacturing. A sheet metal component is usually produced with dies and punches, manufactured in accordance with the shape and dimensions of the component. This conventional method is adequate for mass production because the cost of dies and punches can be shared with a large number of products. Recently, however, new production methods for a small size lot are being developed, since the customer's demand was so diversified that the lot size has become small. Among various methods, using simple tool, small hanll11er or laser, the incremental forming process with simple tool has gained a great attention.